Bay of sighs [compact disc, unabridged] - Roberts, Nora (Roberts, Nora. Guardians trilogy., 2016)
To celebrate the rise of their new queen, three goddesses of the moon created three stars, one of fire, one of ice, one of water. But then they fell from the sky, putting the fate of all worlds in danger. And now three women and three men join forces to pick up the pieces.